Unused potential of abandoned quarries on the example of Wieżyca and Chwałków (Lower Silesia) - Krawczyk, Elżbieta; Lorenc, Marek (Geotourism/Geoturystyka, 2025)
The proper development of abandoned mine workings is the aesthetic, environmental and economic problem. Abandoned quarries are subjected to natural remediation by reconstruction of groundwater table and expansion of plants. Troubles arise when abandoned quarries become illegal landfills and when steep, commonly vertical, unprotected walls, and/or deep reservoirs may become lethal traps. However, the same, hazardous elements: walls and reservoirs can be attractions for both the local residents and the tourists. Values of abandoned quarries were appreciated and developed in the past with positive effects. The authors present examples of two quarries from the vicinity of Ślęża in Lower Silesia, which should encourage us to consider such sites as elements of local economy and to perceive their undeveloped potential.